2000
DOI: 10.1177/107110070002101003
|View full text |Cite
|
Sign up to set email alerts
|

Associated Injuries Found in Chronic Lateral Ankle Instability

Abstract: Sixty-one patients underwent a primary ankle lateral ligament reconstruction for chronic instability between 1989 and 1996. In addition to the ligament reconstruction, all patients had evaluation of the peroneal retinaculum, peroneal tendon inspection by routine opening of the tendon sheath, and ankle joint inspection by arthrotomy. A retrospective review of the clinical history, physical exam, MRI examination, and intraoperative findings was conducted on these 61 patients. The purpose was to determine the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
154
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(170 citation statements)
references
References 30 publications
5
154
1
10
Order By: Relevance
“…The low detection rate for chondral lesions was similar to that found previously with preoperative MRI in a study of athletes with symptomatic ankle lesions, where chondral lesions were detected in five of 26 patients (19%). Other investigators have reported a higher detection rate of chondral lesions on preoperative MRI, with 11 of 14 (79%) chondral lesions observed [2]. However, in that study, ankle exploration was performed without arthroscopy through an anterolateral incision.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The low detection rate for chondral lesions was similar to that found previously with preoperative MRI in a study of athletes with symptomatic ankle lesions, where chondral lesions were detected in five of 26 patients (19%). Other investigators have reported a higher detection rate of chondral lesions on preoperative MRI, with 11 of 14 (79%) chondral lesions observed [2]. However, in that study, ankle exploration was performed without arthroscopy through an anterolateral incision.…”
Section: Discussionmentioning
confidence: 82%
“…A specialized musculoskeletal radiologist may have access to various imaging sequences and may have an extensive background in reading images of musculoskeletal tissue. The high MRI detection accuracy rate in a previous study may be partly attributable to the fact that 60% of the MRIs in that study were performed at the host institution with access to a musculoskeletal radiologist [2].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations